2016
DOI: 10.5114/reum.2016.58754
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of radiation synovectomy (radiosynovectomy or radiosynoviorthesis) with yttrium-90 in exudative inflammation of synovial membrane of knee joints in patients with rheumatic diseases – preliminary report

Abstract: ObjectivesHypertrophic and exudative synovitis of the knee is one of the earliest symptoms in rheumatic diseases. In the case of pharmacotherapy failure, other methods which directly remove the inflamed synovial membrane are used – synovectomies. Radiosynovectomy (RSV) is the radiopharmaceutical application of colloidal solution to joint cavities. In this study, the authors assessed the efficacy of knee radiosynovectomy with yttrium-90 (Y-90) in several groups of patients divided into certain rheumatic disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Presentation of the inflammation in scales allowed for the gradation of symptoms; a statistically significant reduction in clinical symptoms of knee joint inflammation in the 6 th week after the RS was observed, assessed via the Colorado scale (score reduction from 10.9 ±2.7 to 4.66 ±3.18), reduction of the pain VAS from 50 to 10, the illness VAS assessed by the patient/parent from 69.9 ±13.3 to 32.4 ±16.7 and illness VAS assessed by the physician from 68.8 ±12.4 to 36.9 ±16. In Zalewska's study [15], in a group of patients with RA, significant pain reduction was achieved as an early (4 weeks) benefit of RS -this is confirmed in all of the parameters assessed in the pain category of the WOMAC index. Matryba's study [16] showed pain and oedema reduction in patients with RA assessed in the average period of 56 days from knee joint RS in 68.7% of the patients.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Presentation of the inflammation in scales allowed for the gradation of symptoms; a statistically significant reduction in clinical symptoms of knee joint inflammation in the 6 th week after the RS was observed, assessed via the Colorado scale (score reduction from 10.9 ±2.7 to 4.66 ±3.18), reduction of the pain VAS from 50 to 10, the illness VAS assessed by the patient/parent from 69.9 ±13.3 to 32.4 ±16.7 and illness VAS assessed by the physician from 68.8 ±12.4 to 36.9 ±16. In Zalewska's study [15], in a group of patients with RA, significant pain reduction was achieved as an early (4 weeks) benefit of RS -this is confirmed in all of the parameters assessed in the pain category of the WOMAC index. Matryba's study [16] showed pain and oedema reduction in patients with RA assessed in the average period of 56 days from knee joint RS in 68.7% of the patients.…”
Section: Discussionmentioning
confidence: 79%
“…Compared to the US prior to the RS (n = 18) and 6 weeks after the RS; joint exudate was still present (but in low intensity), there were no differences in the assessment of synovial thickening/hypertrophy, but there was significant reduction of synovial hyperaemia, which confirmed the influence of RS on inflammatory activity. In Zalewska's [15] study, in the RA and SpA groups, a significant reduction in synovial hypertrophy was noted at one month after the RS procedure in RA patients, a reduction in the thickness of the synovial membrane from 7.6 ±2.57 mm to 4.71 ±1.85 mm was observed, and a statistically significant reduction in the joint exudate observed, from 8.91 ±3.65 mm to 5.53 ±2.95 mm. In another study US was performed on average 56 days after the RS; joint exudate was found in 76.8% and synovial hypertrophy in 87.5% [16].…”
Section: Discussionmentioning
confidence: 90%
“…Radiosynoviorthesis has been used successfully to treat rheumatoid arthritis, psoriatic arthritis, osteoarthritis, and other arthropathies in humans . Yttrium‐90, 186 Re, and 169 Er, the radionuclides most frequently used, have some shortcomings.…”
Section: Discussionmentioning
confidence: 99%
“…Other radiation doses used for radiosynoviorthesis in humans have varied widely, ranging from 15 MBq of 186 Re for fingers and toes to 925 MBq of 188 Re for knees . Radiosynoviorthesis has been successfully achieved in human knees using 90 Y at radiation doses ranging from 184 MBq to 222 MBq . Erbium‐169, which is frequently used in humans for radiosynoviorthesis of small joints such as interphalangeal joints, has been used at radiation doses ranging from 10 to 40 MBq .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation